2021
DOI: 10.2196/27551
|View full text |Cite
|
Sign up to set email alerts
|

Engaging Parents and Health Care Stakeholders to Inform Development of a Behavioral Intervention Technology to Promote Pediatric Behavioral Health: Mixed Methods Study

Abstract: Background Despite effective psychosocial interventions, gaps in access to care persist for youth and families in need. Behavioral intervention technologies (BITs) that apply psychosocial intervention strategies using technological features represent a modality for targeted prevention that is promising for the transformation of primary care behavioral health by empowering parents to take charge of the behavioral health care of their children. To realize the potential of BITs for parents, research i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…With social distancing and stay-at-home mandates in effect, digital tools that are easily accessible and cost effective offer a solution to help families navigate the stresses of the COVID-19 pandemic. Studies have demonstrated the value of digital interventions in allowing various populations, including families, to access evidence-based guidance on demand and through a modality (web-based) that they are already comfortable using to seek mental, behavioral, and brain health guidance ( Lund et al, 2018 ; Caulfield and George, 2020 ; O’Dell et al, 2021 ). Supplementary to intervention, other tools such as self-paced, at-home brain science education, could offer additional insight for parents seeking to better understand their own brain health.…”
Section: Background/introductionmentioning
confidence: 99%
“…With social distancing and stay-at-home mandates in effect, digital tools that are easily accessible and cost effective offer a solution to help families navigate the stresses of the COVID-19 pandemic. Studies have demonstrated the value of digital interventions in allowing various populations, including families, to access evidence-based guidance on demand and through a modality (web-based) that they are already comfortable using to seek mental, behavioral, and brain health guidance ( Lund et al, 2018 ; Caulfield and George, 2020 ; O’Dell et al, 2021 ). Supplementary to intervention, other tools such as self-paced, at-home brain science education, could offer additional insight for parents seeking to better understand their own brain health.…”
Section: Background/introductionmentioning
confidence: 99%